Insights on antimicrobial resistance, biofilms and the use of phytochemicals as new antimicrobial agents - M. Simões (2015)
Antimicrobial resistance is one of the most serious public health problems. This is of particular concern when bacteria become resistant to various antimicrobial agents simultaneously and when they form biofilms. Consequently, therapeutic options for the treatment of infections have become limited, leading frequently to recurrent infections, treatment failure and increase of morbidity and mortality. Both, persistence and spread of antibiotic resistance, in combination with decreased effectiveness and increased toxicity of current antibiotics have emphasized the urgent need to search alternative sources of antimicrobial substances. Plants are recognized as a source of unexplored chemical structures with high therapeutic potential, including antimicrobial activity against clinically important microorganisms. Additionally, phytochemicals (plant secondary metabolites) present several advantages over synthetic molecules, including green status and different mechanisms of action from antibiotics which could help to overcome the resistance problem. In this study, an overview of the main classes of phytochemicals with antimicrobial properties and their mode of action is presented. A revision about the application of phytochemicals for biofilm prevention and control is also done. Moreover, the use of phytochemicals as scaffolds of new functional molecules to expand the antibiotics pipeline is reviewed. Â(c) 2015 Bentham Science Publishers.